Number of attacks against retailers falls, but the severity and sophistication increase. (January 2015) - Unknown
Abstract : In the run-up to the annual 'Black Friday' and 'Cyber Monday' shopping sprees, pundits in the information security industry were warning that scammers and hackers would also be on the rampage. As it turned out, cyber-attackers actually scaled back their activities on those days, according to research by IBM.